The potential effect of natural compounds from Indonesian spices in alleviating inflammation due to the coronavirus disease (COVID-19): a narrative review - Yuliana, . (Indonesian Journal of Pharmacology and Therapy, 2021)
COVID-19 causes increasing of inflammatory cytokines even cytokine storm in the severe condition. Enhance body immune system is one strategy against COVID-19. Spices in traditional Indonesian cuisine are believed as boost immunity. They contain active compounds such as curcumin, allicin, quercetin and capsaicin which can be used to alleviate inflammation. In this literature review, the potency of curcumin, allicin, quercetin, and capsaicin in alleviating inflammation due the COVID-19 was reported. Literatures were gathered from PubMed, Science Direct, and Google Scholar search engines. COVID-19 causes the increase of proinflammatory cytokine levels such as TNFα and IL-6. Curcumin, allicin, quercetin, and capsaicin regulate the expression of proinflammatory cytokines. These nutritional agonists of peroxisome proliferator-activated receptor-γ (PPAR-γ) showed inhibitory effects on pro-inflammatory cytokines and promote immune cell differentiation into anti-inflammatory phenotypes. Curcumin has an anti-inflammatory effect that can prevent pneumocytes, renal cells, and cardiomyocytes damages. Allicin and quercetin can decrease TNFα and IL-6 levels due to they can increase the superoxide dismutase (SOD) levels. In conclusion, curcumin, allicin, quercetin and capsaicin can enhance body immune system due to their anti-inflammatory effect through down-regulation of the inflammatory cytokines expression. These spices could be used as adjuvant therapy to boost body immune system against COVID-19.